2008
DOI: 10.1002/pssc.200778659
|View full text |Cite
|
Sign up to set email alerts
|

Structural features in GaN grown on a Ge(111) substrate

Abstract: Using electron microscopy, structural characterisation has been carried out on a GaN epilayer grown directly on a Ge(111) substrate using plasma assisted molecular beam epitaxy (PAMBE) without any intermediate buffer layers. It was determined that a defect with a triangular shape, initially observed with optical microscopy, is essentially a faceted void in the Ge extending from the interface into the substrate. Both hexagonal and cubic phase GaN were observed in the epilayer which may be due to temperature var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…Compared with epilayer A, epilayers B and C show a significant reduction in the FWHM for both reflections, indicating improved crystal quality. The bright contrast observed at the bottom of epilayer A (denoted in the box), which is due to the formation of inclined stacking faults in cubic GaN inclusions as determined previously using TEM, 5) is absent in the epilayers B and C. Both selected area diffraction (SAD) and X-ray '-scans reveal no evidence of misorientated domains in epilayers B and C, which are, however, present in epilayer A. 4) The polarity of the GaN epilayers was determined using CBED.…”
supporting
confidence: 62%
See 1 more Smart Citation
“…Compared with epilayer A, epilayers B and C show a significant reduction in the FWHM for both reflections, indicating improved crystal quality. The bright contrast observed at the bottom of epilayer A (denoted in the box), which is due to the formation of inclined stacking faults in cubic GaN inclusions as determined previously using TEM, 5) is absent in the epilayers B and C. Both selected area diffraction (SAD) and X-ray '-scans reveal no evidence of misorientated domains in epilayers B and C, which are, however, present in epilayer A. 4) The polarity of the GaN epilayers was determined using CBED.…”
supporting
confidence: 62%
“…However, characterisation using transmission electron microscopy (TEM) shows many structural defects such as misorientated domains 4) and cubic GaN inclusions, in addition to a high density of threading dislocations (TDs). 5) Further research has found that the crystal quality of the GaN epilayer can be improved if step-flow growth on a Ge(111) substrate is enhanced using either a miscut substrate or a higher growth temperature, i.e., above 800 C. 6) Extensive structural characterisation of the improved GaN epilayers has been carried out using X-ray diffraction (XRD) and TEM, and the results are presented in this paper.…”
mentioning
confidence: 99%
“…5. These defects have previously been identified by TEM as being voids in the Ge substrate [7] and can be observed with an optical microscope because GaN is transparent to visible wavelengths. The triangular shape of these voids indicates the etching process is selective with respect to the Ge crystal orientation.…”
Section: Introductionmentioning
confidence: 97%
“…During the growth, voids are present at the top of the Ge surface, resulting from Ge diffusion into the GaN. 30 In addition, we have performed cathodoluminescence (CL) measurements at RT at 5 kV in a Philips XL30 equipped with a Gatan MonoCL4 system. The SEM image, the corresponding integrated CL-spectrum, and a set of monochromatic CL intensity images of sample E are shown in Fig.…”
Section: Optical Characterizationmentioning
confidence: 99%